Clinical and radiographic variables related to implants with simultaneous grafts among type 2 diabetic patients treated with different hypoglycemic medications: a retrospective study - Shaojie Shi; Feng Ding; Xiangdong Liu; Lei Wang; Xingxing Wang; Sijia Zhang; Guoqiang Zhao; Yingliang Song (BMC, 2021)
Abstract Background The influence of different hypoglycemic agents on peri-implant variables among type 2 diabetes mellitus patients is still unclear. Therefore, the aim of this study was to assess the radiographic marginal bone loss and clinical parameters around implants in patients using different hypoglycemic agents. Methods In this retrospective cohort study, the dental implant records of type 2 diabetes mellitus patients who met the inclusion criteria were collected. The patients using only single medication as follows: insulin, metformin, or glucagon-like peptide-1 (GLP-1) drugs, were grouped according to their medication. These patients received implant placement with the same initial status, and all the prosthesis restorations were cement-retained ceramic crowns. The peri-implant marginal bone levels were evaluated by periapical radiographs immediately after implant placement and at 1 and 2-year follow-up visits. The baseline characteristics were compared among groups. The peri-implant radiographic marginal bone loss and clinical parameters were preliminarily compared using the Kruskal-Wallis test, and then the covariates were controlled by covariance analysis. Bonferroni post hoc adjustment test was performed for the multiple comparisons. Results After a review of more than 7000 medical records, a total of 150 patients with 308 implants at 1-year follow-up were assessed. The peri-implant marginal bone loss in the GLP-1 drug group was significantly smaller than the insulin group and metformin group (P < 0.01). The radiographic bone loss in the metformin group was higher than the insulin group (P < 0.05). Some of these included patients were lost to follow-up. Only 74 patients with 129 implants completed the 2-year follow-up. The radiographic bone loss in the metformin group was still higher than the insulin group (P < 0.05) and GLP-1 group (P < 0.01). There was no significant difference in the BOP (+) and the mean PD among groups (P > 0.05). Conclusions The radiographic variables were not exactly the same among the patients with different hypoglycemic agents at both the 1 and 2-year follow-ups. After ensuring consistency in baseline characteristics, the positive effect of GLP-1 drugs on peri-implant bone remodeling may be no less than insulin or metformin. More studies are needed to verify the direct effect of these drugs on peri-implant bone. Clinical trial registration number ChiCTR2000034211 (retrospectively registered).